Pondering Mohammed Abed Al-Jabri’s Project of an ‘Arab Reason’ - López-Farjeat, Luis Xavier (MDPI AG, 2026)
Mohammed Abed Al-Jabri (d. 2010) is one of the most important and stimulating contemporary Arabic philosophers. He is well-known for his project Critique of Arab Reason (Naqd al-ʿaql al-ʿArabī), in which he deconstructs the Arabic philosophical and cultural tradition, revitalizing the rationalist legacy of the classical period, mainly, the philosophical ideas of Ibn Rushd (Averroes). According to Al-Jabri, the renewal of Arab thought requires a non-traditionalist understanding of tradition. In this paper, I shall critically examine Al-Jabri’s “contextualist” methodology. I first provide some historical background for understanding Al-Jabri’s concern with fostering a critique of Arab reason. Secondly, I discuss the way Al-Jabri reinterprets Islamic intellectual history, emphasizing his attempt to overcome the idiosyncratic approaches to Arab culture, namely, religious Salafists, Orientalists, and left nationalists. Thirdly, I discuss the extent to which his renewal of classical intellectual tradition, mainly his approach to Ibn Rushd, allows for the socio-political and cultural reformation of an Arab identity through his idea of “understanding oneself through the other.” Finally, I highlight some successful aspects of Al-Jabri’s epistemic project and its potential relevance for the present. ©The author ©MDPI.
Keywords: Mohammed Abed Al-Jabri; Arab–Islamic intellectual history; Islamic philosophy; Ibn Rushd (Averroes); Averroes; Arab reason; Nahḍa (Arabic renaissance); Salafism; Orientalism; Arabic leftist nationalisms; European modernity; Arab identity